Anti-tumoral effect of the mitochondrial target domain of Noxa delivered by an engineered Salmonella typhimurium. - Jae-Ho Jeong; Kwangsoo Kim; Daejin Lim; Kwangjoon Jeong; Yeongjin Hong; Vu H Nguyen; Tae-Hyoung Kim; Sangryeol Ryu; Jeong-A Lim; Jae Il Kim; Geun-Joong Kim; Sun Chang Kim; et al. (PLoS ONE, 2014)
Bacterial cancer therapy relies on the fact that several bacterial species are capable of targeting tumor tissue and that bacteria can be genetically engineered to selectively deliver therapeutic proteins of interest to the targeted tumors. However, the challenge of bacterial cancer therapy is the release of the therapeutic proteins from the bacteria and entry of the proteins into tumor cells. This study employed an attenuated Salmonella typhimurium to selectively deliver the mitochondrial targeting domain of Noxa (MTD) as a potential therapeutic cargo protein, and examined its anti-cancer effect. To release MTD from the bacteria, a novel bacterial lysis system of phage origin was deployed. To facilitate the entry of MTD into the tumor cells, the MTD was fused to DS4.3, a novel cell-penetrating peptide (CPP) derived from a voltage-gated potassium channel (Kv2.1). The gene encoding DS4.3-MTD and the phage lysis genes were placed under the control of PBAD , a promoter activated by L-arabinose. We demonstrated that DS4.3-MTD chimeric molecules expressed by the Salmonellae were anti-tumoral in cultured tumor cells and in mice with CT26 colon carcinoma.